Implementation Science Practical at SMP Negeri 1 Sambi, Boyolali, Indonesia - Ibrahim, Abdullah Falak Nabhan; Kusumadani, Annur Indra (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Low frequency and minimal practicum facilities have become the main problems in the implementation of science learning at SMP Negeri 1 Sambi, Boyolali. According to the Minister of National Education Regulation Number 24 of 2007, the learning process requires facilities and infrastructure that support optimal implementation. The benefits of science practicum include increasing students’ motivation to learn science and providing opportunities for them to satisfy their curiosity through scientific approaches. The purpose of this research is to examine the implementation of science practicum and to evaluate the quality of the facilities and infrastructure of the science laboratory at SMP Negeri 1 Sambi, Boyolali. This study used a descriptive qualitative method with data collected through observation, documentation, interviews, and questionnaires. The results show that the quality of facilities and infrastructure for science practical activities at SMP Negeri 1 Sambi, Boyolali is classified as good, as stated in the Minister of National Education Regulation Number 24 of 2007, with an average percentage of 71.62%. The implementation of science practicum is categorized as very good, with an average percentage of 97.8%. The results of the questionnaire also show that 93.4% of the science practicums fall into the very good category, meaning that the implementation of science practicum for Grade VIII in the odd semester runs well.